1999
DOI: 10.1103/physrevlett.82.505
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of the Optical Gamma Ray Decay inT229h

Abstract: Optical measurements of a clean, 2-mC 233 U sample were made to verify light emission from gamma ray decay of the first excited nuclear level in 229 Th. The results showed that the light observed in earlier studies was likely to be caused by alpha-particle induced fluorescence of air. In vacuo, no light emission was discernable. The 229 Th system, therefore, does not appear to provide the level of access for studying atomic-nuclear interactions suggested by the previous measurements. [ S0031-9007(98)08232-5] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 15 publications
(22 reference statements)
0
41
0
Order By: Relevance
“…III, the chemical environment can significantly affect the half-life of the isomeric state [3]. It most likely explains why, given the currently accepted value for the isomeric transition energy, that many previous experiments performed in powders, solids and solutions produced null results [52][53][54][55][56]; similarly, non-VUV sensitive measurements could have been affected by internal conversion [57,58]. The internal conversion process could also have strong implications for the experiments reported in Refs.…”
Section: Importance Of the Electronic Conversion Decay Channelmentioning
confidence: 99%
“…III, the chemical environment can significantly affect the half-life of the isomeric state [3]. It most likely explains why, given the currently accepted value for the isomeric transition energy, that many previous experiments performed in powders, solids and solutions produced null results [52][53][54][55][56]; similarly, non-VUV sensitive measurements could have been affected by internal conversion [57,58]. The internal conversion process could also have strong implications for the experiments reported in Refs.…”
Section: Importance Of the Electronic Conversion Decay Channelmentioning
confidence: 99%
“…In early experiments, two false detections of the decay of the isomer following α-decay of 233 U were reported [12,13], but it was quickly clarified that the observed light was luminescence induced by the background of α-radiation [14,15]. All further attempts at a direct observation of the optical transition failed.…”
Section: The Low-energy Isomer Ofmentioning
confidence: 99%
“…Recoil nuclei: The 229 Th isomer is populated with about 2% probability in the α-decay of 233 U and early attempts at an optical detection of the isomer decay have looked for light emission from 233 U sources [12,13], without success because of a strong background of radioluminescence [14,15]. This problem can be mitigated by using 229 Th recoil nuclei: If the α-decay of 233 U occurs close to the surface of the sample, the freshly produced 229 Th may be ejected and can be collected on an absorber (such as CaF 2 or MgF 2 , for instance) placed in front of the 233 U.…”
Section: Experimental Search For the 229 Th Nuclear Transitionmentioning
confidence: 99%
“…Their observed value for the isomeric transition were 3.5 eV [159] and likely 4 eV [160], respectively. However, in 1999, the studies of three different groups indicated that these conclusions must be based on the incorrect interpretation of experimental data [161][162][163]. G. M. Irwin and K. H. Kim later 5.1 Introduction of the agreed that their observation might result from the α-particle induced fluorescence of air, actually N 2 , surrounding the sample [161,162,164].…”
Section: Thorium Nucleusmentioning
confidence: 99%